Risk Analysis and Portfolio Modelling - Allen, David; Luciano, Elisa (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Financial Risk Measurement is a challenging task, because both the types of risk and the techniques evolve very quickly. This book collects a number of novel contributions to the measurement of financial risk, which address either non-fully explored risks or risk takers, and does so in a wide variety of empirical contexts.
English
Keywords: risk assessment; mortgage portfolio; insider trade; contagion effect; risk capital; liquidity risk; hedonic modeling; rolling wavelet correlation; inverse coefficient of variation; exchange traded funds; sovereign risk/debt; securitized real estate and local stock markets; portfolio optimization; portfolio analysis; risk premium; performance measurement; risk analysis; contagion; outperformance probability; Sharpe ratio; probability of default; small and medium enterprises; RAROC; sovereign defaults; risk attribution; multiresolution analysis; credit ratings; debt maturity structure; herding; asset-backed securities; modern portfolio theory; housing segments; analytic hierarchy process; African countries; Asian firms; decentralization; credit scoring; dependence; mutual funds; spillover effect; capital allocation; copulas; matched filter; institutional holding; crop insurance; factor investing; wavelet coherence and phase difference; risk; value-at-risk; rearrangement algorithm